2013
DOI: 10.1111/cns.12177
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Depression Behavioral Criteria in Cynomolgus Monkeys

Abstract: Depression is a common mental disorder with relatively high lifetime prevalence and substantial disability, especially in women [1][2][3]. Clinical manifestations of depression include loss of interest or pleasure, disturbed sleep or appetite, poor concentration, etc., worst of which is suicide. To solve such an important global public health issue, it is essential to establish ideal animal models for study and treatment of depression. Cynomolgus monkeys have been proved to be advantageous for modeling human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Less sucrose consumption was observed in adult rhesus macaques following chronic glucocorticoid exposure 29 , a model of depressive-like behavior, while more was observed in adolescent monkeys that demonstrated depressive-like behaviors following social isolation 30 . Recently, Fan et al reported that the attempt for apple test (AAT) appeared to reliably measure anhedonia in cynomolgus monkeys 23 . In our study, SPT and AAT were both conducted to examine anhedonia, but only the AAT differentiated between the control and stressed groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less sucrose consumption was observed in adult rhesus macaques following chronic glucocorticoid exposure 29 , a model of depressive-like behavior, while more was observed in adolescent monkeys that demonstrated depressive-like behaviors following social isolation 30 . Recently, Fan et al reported that the attempt for apple test (AAT) appeared to reliably measure anhedonia in cynomolgus monkeys 23 . In our study, SPT and AAT were both conducted to examine anhedonia, but only the AAT differentiated between the control and stressed groups.…”
Section: Discussionmentioning
confidence: 99%
“…We measured body weight and sucrose preference test (SPT) 22 at baseline and the end of each stress cycle. In addition, the attempt for apple test (AAT) 23 and human intruder test (HIT) 24 were conducted at the end of the five stress cycles. In the AAT, the fewer attempts for apples than controls was considered as anhedonia, which is a core symptom of patients with depression 23 .…”
Section: Behavioral Observations and Testsmentioning
confidence: 99%
See 1 more Smart Citation